Crenças, práticas de cuidado e prevenção acerca das DST/AIDS na atenção básica à saúde - Pereira, Lidianny Braga (2012)
The response to the emergence of Aids in Brazil potentiated several actions in the health services, so as to ensure quality care, early diagnosis and safe and effective treatment to the population. So, as soon as the HPS (Health Public System) went on to give attention to the needs brought about by the demands of STD/Aids, being the Basic Care (BC), strategically, the largest space for the implementation of a policy of prevention and care of these, since it is the user's preferred input port on the system. In this sense, this study aimed to investigate the care and prevention care and prevention about STD/Aids in Family Health Units (FHU), from the beliefs and practices of the professionals. From a stratified sampling for convenience, have been selected 19 FHU, located in the city of Joao Pessoa-PB, attending a professional at FHU, with ages ranging from 23 to 65 years (M=40; SD=10,63), being only one male. We used three instruments that complemented: structured questionnaire, screenplay submissions and semi structured interview. The data of the questionnaire and of the screenplay were analyzed through descriptive statistics, while the interviews were transcribed and then held a thematic category analysis. From quantitative data, it was found that 11 FHU perform meet the STD from a syndromic approach, although they deal with that treatment is done in specialized services, most of the STD. On the diagnosis, no FHU offers anti-HIV, VDRL tests and serology for Hepatitis B and C. About the availability of male condom, 18 FHU said always have it available to the population, being the free distribution in 12 of them. The populations considered most vulnerable to STD/Aids were women and adolescents/young, although in some USF, prevention activities with them. External activities of prevention were referred by 13 FHU, being the school the most quoted (11 FHU). It was noted that in 9 FHU condoms were available at the reception desk; only in a unit had educational brochures distribution and in 4 had this briefs posters theme. As for qualitative data, the speeches of professionals pointed to 2 thematic classes: 1) HIV infection (Categories: Contagion and Individual HIV seropositivity); and 2) Perceptions and practices in the workplace (Categories: Perception of care, Training in management of STD/Aids, STD/Aids in BC to health, Management of HIV/Aids and Demand). The speeches of professionals revealed, on the one hand, stereotypical beliefs and biased against the person living with HIV/Aids and own illness, and on the other, the speeches referred to the importance of an effective care practice against the STD/Aids and to include that issue in the service routine. Points to the need for commitment and accountability of management, organizing the definition of priorities on the schedule of BC and ensuring the required training and inputs that have the human and material resources at FHU for working with the STD/Aids.